Why Silver Deposition is so Fast: Solving the Enigma of Metal Deposition - Pinto, Leandro M. C. (2013)
A perfect match: Silver deposition is one of the fastest electrochemical reactions, even though the Ag+ ion loses more than 5 eV solvation energy in the process. This phenomenon, an example of the enigma of metal deposition, was investigated by a combination of MD simulations, DFT, and specially developed theory. At the surface, the Ag+ ion experiences a strong interaction with the sp band of silver, which catalyzes the reaction.